Der digitale Euro: Chancen und Risiken einer digitalen Notenbankwährung - Roland Broemel; Alexander Meyer-Gohde; Volker Wieland (Wirtschaftsdienst, 2023)
Im Euroraum wird die Einführung eines digitalen Euro bereits seit Längerem diskutiert. Die Untersuchungsphase der Europäischen Zentralbank lief bereits seit Oktober 2021 und ging im Oktober 2023 in eine Vorbereitungsphase über. In anderen Ländern wird digitales Zentralbankgeld bereits genutzt. Hinsichtlich der Einführung eines digitalen Euro ergeben sich viele Fragen, die Haushalte und Unternehmen, Geschäftsbanken sowie die Zentralbank betreffen. Unter anderem stellen sich folgende Fragen: Wozu braucht man in der heutigen Zeit eine digitale Zentralbankwährung? Welche Anforderungen muss eine zusätzliche Geldform erfüllen, die von einer Zentralbank emittiert wird? Welche Risiken und Chancen ergeben sich mit dem digitalen Euro? – – Central banks including the ECB have moved forward with plans concerning a central bank digital currency (CBDC) to bemade available to the public at large. In particular, the announcement of a private stable coin by a consortium led by Facebook/Metahad served as a catalyst. Perhaps the fear of losing market share in terms of seigniorage or impairment of monetary policy played a role.By now, however, a widely-expressed criticism is that the CBDC constitutes a solution that is still in search of a problem to be solved.The argument put forth by the ECB that a CBDC is needed as a monetary anchor in the digital sphere carries little weight after closerinspection. Furthermore, potential advantages of a CBDC are partly reduced or precluded because of constraints imposed in order tominimise potential risks for the stability of the banking system and the business model of banks. For example, the model pursued bythe ECB refrains from positive or negative interest rates paid on CBDC, imposes limits on transaction amounts and precludes a store ofvalue function. At this point, the main potential benefit appears to be a possible reduction of transaction costs in digital payments and apossible contribution to keeping platform-based markets in digital ecosystems contestable. It remains an open question whether this isa task for central banks.
Keywords: E40; E42; 330; Euro; Virtuelle Währung; Zentralbank; Euro; Virtuelle Währung; Zentralbank